Effectiveness Performance of Sodium Hypochlorite (NaOCl) to Increase Hatchability of KUB Chicken Eggs in Artificial Hatchery - Jonathan Anugrah Lase; Aulia Rahmad Hasyim; Alwiyah Alwiyah; Surya Surya; Suroto Suroto; Mustafa Hutagalung; Siti Maryam Harahap; Khadijah el Ramija; Dian Lestari; Verika Armansyah Mendrofa (Buletin Peternakan, 2023)
This study aims to determine the effect of 40°C warm water and sodium hypochlorite solution (NaOCl) on the hatchability of KUB chickens through artificial hatchery. The NaOCl concentrations used in this study were 0.25% and 0.5%. The hatching eggs used are the production of KUB hens which are kept intensively in the UPBS Poultry Departmen, Assessment Institute for Agricultural Technology (AIAT) of North Sumatra. The research procedures applied in this study were collection of hatching eggs, fumigation of machines and equipment, setting of machines and hatching eggs, washing of eggs with cherry leaf extract and hatching of eggs for 21 days. During the hatching process, observations were made on the variables that had been determined. The observed variables were egg shape index, egg weight loss, shell temperature and hatchability. The method used was a completely randomized design (CRD) with 3 treatments and 300 replications. The results showed that the shape index of the eggs that hatched in this study was 76.71 - 77.38%, the P2 treatment experienced the most stable weight loss compared to other treatments. The conclusion in this study P2 (0.25% NaOCl) effective in the highest egg hatchability.